1999
DOI: 10.1128/mcb.19.1.646
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-Dependent Regulation of Human DNA Polymerase α-Primase Activity by Phosphorylation

Abstract: DNA polymerase ␣-primase is known to be phosphorylated in human and yeast cells in a cell cycledependent manner on the p180 and p68 subunits. Here we show that phosphorylation of purified human DNA polymerase ␣-primase by purified cyclin A/cdk2 in vitro reduced its ability to initiate simian virus 40 (SV40) DNA replication in vitro, while phosphorylation by cyclin E/cdk2 stimulated its initiation activity. Tryptic phosphopeptide mapping revealed a family of p68 peptides that was modified well by cyclin A/cdk2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 59 publications
8
99
0
Order By: Relevance
“…Alternatively, because p68 itself binds SV40 TAg (32,34,56), active complex formation may require a particular coordination between the interactions of p180 and p68 with TAg, which might be disturbed when the two subunits are derived from different species. Abundant evidence exists that p68 acts as a regulator of DNA polymerase ␣-primase (36,(55)(56)(57)(58), but the suppression of Mp180 C terminus-induced inhibition of SV40 DNA replication by Mp68 is only partial and is not evident in complexes such as (H671M)MH 2 and M 2 H 2 ( Fig. 6A and Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, because p68 itself binds SV40 TAg (32,34,56), active complex formation may require a particular coordination between the interactions of p180 and p68 with TAg, which might be disturbed when the two subunits are derived from different species. Abundant evidence exists that p68 acts as a regulator of DNA polymerase ␣-primase (36,(55)(56)(57)(58), but the suppression of Mp180 C terminus-induced inhibition of SV40 DNA replication by Mp68 is only partial and is not evident in complexes such as (H671M)MH 2 and M 2 H 2 ( Fig. 6A and Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Our results argue for the latter, as cyclin A could be shown to stimulate Pol ␦-dependent DNA synthesis. Furthermore, it was recently reported that Pol ␣-dependent initiation of SV40 DNA replication in vitro was stimulated by cyclin E͞cdk2, but inhibited by cyclin A͞cdk2 (40). Thus, by concomitantly inactivating Pol ␣-associated functions and activating Pol ␦ and͞or some of its cofactors, cyclin A may contribute to the switch from Pol ␣-dependent initiation to Pol ␦-driven strand elongation.…”
Section: Discussionmentioning
confidence: 99%
“…10), raises the question whether the initiation of leading and lagging strand replication are controlled by different mechanisms. With the recombinant replication proteins in hand and with the known regulation of leading strand initiation by cyclin-dependent kinases (52,75,76), this question can now be addressed.…”
Section: Figmentioning
confidence: 99%